2015
DOI: 10.1182/blood-2014-11-611905
|View full text |Cite|
|
Sign up to set email alerts
|

Targeted downregulation of platelet CLEC-2 occurs through Syk-independent internalization

Abstract: Key Points• CLEC-2 can be downregulated from circulating platelets by anti-CLEC-2 antibodies through Src-family kinasedependent internalization.• Platelet-specific Syk deficiency abrogates anti-CLEC-2 antibodies-induced thrombocytopenia, but not CLEC-2 internalization.Platelet aggregation at sites of vascular injury is not only essential for hemostasis, but may also cause acute ischemic disease states such as myocardial infarction or stroke. The hemi-immunoreceptor tyrosine-based activation motif-containing C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 41 publications
1
33
2
Order By: Relevance
“…showed that CLEC‐2 platelet levels can be decreased in vivo by administering anti‐CLEC‐2 monoclonal antibody, INU1 . INU1‐induced CLEC‐2 immunodepletion is mediated by Src family kinase‐dependent receptor internalization in vitro and in vivo , presumably followed by intracellular degradation . We generated rat anti‐mouse CLEC‐2 monoclonal antibody, 2A2B10.…”
Section: Resultsmentioning
confidence: 99%
“…showed that CLEC‐2 platelet levels can be decreased in vivo by administering anti‐CLEC‐2 monoclonal antibody, INU1 . INU1‐induced CLEC‐2 immunodepletion is mediated by Src family kinase‐dependent receptor internalization in vitro and in vivo , presumably followed by intracellular degradation . We generated rat anti‐mouse CLEC‐2 monoclonal antibody, 2A2B10.…”
Section: Resultsmentioning
confidence: 99%
“…Endocytosis of purinergic receptors e.g ., P2Y 1 and P2Y 12 , mediates their resensitization [11]. Endocytosis of C-type Lectin Receptor-2 (CLEC-2) and Thrombopoietin receptor (Mpl/TPOR) regulates their surface levels and downstream signaling [12, 13]. These data clearly show that endocytosis has significant importance in platelet physiology.…”
Section: Introductionmentioning
confidence: 99%
“…We used outbred strain CD1 or the inbred strain C57BL/6 as well as the transgenic strains Gp6 −/− (Bender et al, 2011), Itga2 −/− (Holtkotter et al, 2002), Lat −/− and Syk fl/fl, Pf4−Cre+/− (Lorenz et al, 2015) (all C57BL/6 background) as indicated. Male and female mice of 6 to 12 weeks were used in equal numbers for all experiments, unless stated otherwise.…”
Section: Animals and Husbandrymentioning
confidence: 99%